Seasonal variation of denitrification in tropical forage grasses - Souto, Sebastião Manhães; Johanna Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out to study the seasonal pattern of nitrate dissimilation on roots of tropical forage grasses under frequent nitrate applications. The grasses used were: Hyparrhenia rufa, Digitaria decumbens (cvs. Pangola A-21 and Transvala) and Pennisetum purpureum (cvs. Napier and Cameron). Denitrification was determined by the accumulation of N2O in an atmosphere containing C2H2, 17 h after the application of 20 ml of a 20 nM N-NO3 solution. Genotype and N fertilization effects on denitrification were observed up to 4 weeks after each cutting of the grasses and N addition. Denitrification varied with the plant genotypes and the season. The Pennisetum spp. denitrified more at the beginning of the rainy season while denitrification associated with the Digitaria spp, was highest during the dry season, when all NO3 applied for the test was lost as N2O within 17 hours.